Akselerasi Upaya Mengoptimalkan Partisipasi Politik Masyarakat dalam Menghadapai Pemilu Tahun 2024: Studi: Komisi Pemilihan Umum (KPU) Kota Blitar - Evita Sari, Ayu; Hadi, Krishno (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
Ahead of the 2024 election, the Blitar City KPU must be able to ensure that the political participation of the community can achieve the set targets and goals. This is because people's political participation is not only an important indicator for the success of a program and policy but also as a form of community participation in preventing and avoiding deviant acts, especially in an election process. The purpose of this study was to find out the efforts and strategies being carried out by the KPU of Blitar City in optimizing the political participation of the people in the upcoming 2024 elections. The research was conducted using a qualitative method through literature reviews on various literature sources that are directly related to related titles including journals, books, and official sources, as well as joint interviews with the KPU of Blitar City. The results of this study indicate that the Blitar City KPU as a stakeholder has carried out various methods and strategies to increase the political participation rate in Blitar City, especially in welcoming the upcoming 2024 elections. In general, the programs implemented have represented the attention of the KPU and the government on the importance of community participation both for voter turnout and measures to prevent irregularities and manipulation.